Evolutionary genetics - Smith, John Maynard (Oxford Univ. Press, 1999)
The book covers basic population and quantative genetics, evolutionary game theory, behavioural evolution, sexual selection and mating systems, speciation, and macroevolution. Theory and mathematics are clearly explaned, with the aid of problems at the end of chapters.